Semantics Analysis of Sentence, Utterance, and Proposition in“Dear My Emotions” - Putri Cidi Adhisty; Hilma Safitri; Dimas Prasetyo; Devano Andhi Saputra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research describes and identifies narratives within the framework of the semantic structures of the book "Dear My Emotions" as narratives comprising sentences, utterances, and presuppositions. Employing descriptive qualitative techniques, the study analyzes samples from stories such as "Big Dreams," "The Mystery," "Beautiful Sadness," and "Sadness Love," totaling twenty data samples. The analysis reveals how diverse emotional expressions and the profundity of the narratives are intricately displayed through different syntactic and pragmatic forms, thereby enhancing communication and interaction with the readers. The work integrates semantics and discourse by showing how emotional aspects are related to the structural elements of a literary work